PENGARUH KUALITAS LAPORAN KEBERLANJUTAN DAN AUDIT TENURE TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN AUDIT EFFORT SEBAGAI VARIABEL MODERASI - Idawati, Wiwi; Permana, Larasati Kartika (Universitas Multimedia Nusantara, 2024)
Abstract - This study is a quantitative research that aims to examine the effect of sustainability reporting quality and Audit tenure on financial reporting quality with audit effort as a moderating variable. The research uses secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2020-2021. Sampling criteria used a purposive sampling method which obtained a total of 64 samples from 32 manufacturing companies. Testing the hypothesis in this study uses a multiple linear regression model. The research model was processed and tested using STATA Ver.16. The results of this study are: 1) Sustainability reporting quality does not influence financial reporting quality. 2) Audit tenure has a significant positive influence on financial reporting quality. 3) Effort Audit strengthens the effect of the Sustainability reporting quality on financial reporting quality. 4) Audit effort strengthens the effect of Audit tenure on financial reporting quality. Keywords: Financial Reporting Quality; Sustainability Reporting Quality; Audit Tenure; Audit Effort